2016
DOI: 10.1073/pnas.1606290113
|View full text |Cite
|
Sign up to set email alerts
|

Siderophore-based immunization strategy to inhibit growth of enteric pathogens

Abstract: Infections with Gram-negative pathogens pose a serious threat to public health. This scenario is exacerbated by increases in antibiotic resistance and the limited availability of vaccines and therapeutic tools to combat these infections. Here, we report an immunization approach that targets siderophores, which are small molecules exported by enteric Gram-negative pathogens to acquire iron, an essential nutrient, in the host. Because siderophores are nonimmunogenic, we designed and synthesized conjugates of a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
82
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(83 citation statements)
references
References 48 publications
1
82
0
Order By: Relevance
“…Siderophores have been used to develop vaccines and have been covered extensively (80)(81)(82)(83)(84). Bergeron and colleagues reported the use of a vibriobactin analogue linked to either ovalbumin (OVA) or bovine serum albumin (BSA) and their ability to promote antibody production in mice (85).…”
Section: Pharmacological and Medical Applicationsmentioning
confidence: 99%
“…Siderophores have been used to develop vaccines and have been covered extensively (80)(81)(82)(83)(84). Bergeron and colleagues reported the use of a vibriobactin analogue linked to either ovalbumin (OVA) or bovine serum albumin (BSA) and their ability to promote antibody production in mice (85).…”
Section: Pharmacological and Medical Applicationsmentioning
confidence: 99%
“…Another iron-based antimicrobial approach exploits siderophores that have been naturally or synthetically conjugated to antibiotics, tricking microbes into taking up the antibiotic along with the siderophore [3]. A third siderophore-based strategy, priming the host to make anti-siderophore antibodies that may prevent microbes from acquiring iron, has recently taken a giant leap forward [4]. …”
mentioning
confidence: 99%
“…This and other observations suggested that vaccinating against siderophores may confer protection against pathogens that require them. Recently a team of microbiologists and chemists took the next major step [4]. Sassone-Corsi et al .…”
mentioning
confidence: 99%
See 2 more Smart Citations